PERAN KEPALA SEKOLAH DALAM IMPLEMENTASI KURIKULUM MERDEKA BELAJAR DI SDN GUNUNG BUNDER 1 - Rahmi, Sri; Rahmawati, Ima; Mustagfiroh, Siti (PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM, 2022)
This study aims to describe the role of school principals in the implementation of the Independent Curriculum at SDN Gunung Bunder 1. The approach used is qualitative with a case study method. Data collection techniques are carried out through in-depth interviews, observations, and documentation. The results of the study show that school principals play an active role as learning leaders who encourage teachers to develop flexible and contextual learning in accordance with the principles of the Independent Curriculum. The principal also plays a role in fostering collaboration between teachers, conducting academic supervision, and establishing partnerships with parents and the community. Despite being faced with obstacles such as limited initial understanding of teachers and digital means, the principal was able to overcome these challenges through a participatory internal school strategy. A strong and adaptive leadership role is the key to the success of the implementation process of the Independent Curriculum in this elementary school environment.